Analysis of the Relationship Between Vo2Max Level and the Achievement of Tennis Athletes in Semarang City - Maziliyyah Nurlaily Sulistyanto; Wicaksono, Anggit (Universitas Negeri Semarang, 2025)
Introduction: Tennis is an intermittent high-intensity sport that requires optimal aerobic endurance to maintain performance throughout long and demanding matches. Objectives: This study aims to determine the relationship between maximum aerobic capacity (VO2Max) and the achievement of KONI tennis athletes in Semarang City. Method: This research is a quantitative research with a survey method with a correlational approach. The population in this study is KONI tennis athletes in the age group of 12-18 years. The sampling technique used purposive sampling with a total of 11 athletes. Since the achievement rankings between male and female athletes are different, the data is divided into 2 consisting of 5 male and 6 female athletes. The VO2Max data used is secondary data obtained from the results of the MFT test conducted by KONI Semarang City. Meanwhile, to get data on athletes' achievements on a national scale, using the www.pelti.org website. The data analysis technique used the Pearson Product Moment Correlation Test. Result: The results of the study showed: 1. The results of the data analysis of KONI Semarang City men's tennis athletes showed significant values in the variables VO2Max and Achievement, namely 0.000 < 0.05 so that the variables VO2Max and Achievement had a relationship or correlation, 2. The results of the data analysis of KONI Semarang City women's tennis athletes showed significant values in the variables VO2Max and Achievement, namely 0.014, meaning 0.014 < 0.05 so that the variables VO2Max and Performance are related or correlate. Conclusion: Based on the data above, it can be concluded that there is a relationship between VO2Max and the achievements of KONI tennis athletes in Semarang City.